Social responsibility, sustainability and innovation in the Brazilian sugar-energy sector: Trends and perspectives (Research, Society and Development, 2021)
It is undeniable the space that Social Responsibility and other related topics such as Sustainability and Innovation have conquered in academic discussions and in society in general, especially in the face of global economic, social, political and environmental changes, whose positive activities and actions contribute greatly to the expansion of social well-being and / or organizations. In this context, the objective of this study emerged to present an overview of, trends and perspectives of the sugar-energy sector for the next decade, having as scope the Content Analysis (AC), in this case, focused on the literature review on topics such as Social Responsibility, Social and Environmental Responsibility, Sustainability, Technological Innovation and others, involved in the sugar and alcohol production sector in the country. Methodologically, a research with a qualitative approach was conducted, treated and validated by IRAMUTEQ, via Similitude Analysis and word frequency. The results obtained demonstrate that the objective was achieved, both through the bibliographic and documentary review, which made it possible to characterize the research variables by differentiating the use of theoretical models that proved to be adequate to reality and that could be explored in other studies.